2005
DOI: 10.1021/ie050875s
|View full text |Cite
|
Sign up to set email alerts
|

Calculating the Phase Behavior of Gas-Hydrate-Forming Systems from Molecular Models

Abstract: We describe a calculation of the phase behavior of the methane-water system, including the structure-I hydrate phase, starting from a model of the intermolecular forces in the system and using Monte Carlo simulations and theory. The approach we use differs from previous calculations of methane hydrate phase behavior in that it does not treat the water molecules in the hydrate as a static or harmonic lattice, i.e., thermal fluctuations are fully incorporated. Our approach is quite general, but we illustrate it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(46 citation statements)
references
References 69 publications
4
42
0
Order By: Relevance
“…65 This work has shown that this simple model can reproduce all the qualitative features of the phase diagram. Phase diagram calculations for more realistic models with the goal of achieving more quantitative agreement with experimental phase behavior are underway.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…65 This work has shown that this simple model can reproduce all the qualitative features of the phase diagram. Phase diagram calculations for more realistic models with the goal of achieving more quantitative agreement with experimental phase behavior are underway.…”
Section: Discussionmentioning
confidence: 85%
“…The first model was chosen in answer to the question of what might be the simplest molecular model that could describe hydrate behavior. 65 This is a mixture of a hard spheres representing the methane molecule and associating hard spheres (primitive model of water, PW) representing waterswe refer to this as the PW/ HS model. This model has been used extensively by Nezbeda and co-workers 81,85 in applications to aqueous solutions of alkanes, and the solid-fluid equilibrium of the PW has been previously studied for two ice phases.…”
Section: Molecular Models and Monte Carlo Simulationsmentioning
confidence: 99%
“…Here we demonstrate a method by which this chemical potential may be determined accurately. This method of calculation is in the same spirit as those employed in recent work by Monson et al 29,30 who tested the predictions of van der Waals theory against those of more accurate GCMC ͑Grand Canonical Monte Carlo͒ simulation to see what effect the various approximations of the van der Waals-Platteeuw theory had on the estimation of the hydrate guest occupancies.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 For this reason, the possibility of recovering methane stored in the form of hydrates, for energetic purposes, is receiving increasing attention and simulation and theoretical studies of methane hydrates are becoming more and more popular in recent years. [7][8][9][10][11][12][13][14] A review of each of these areas may be found in two recent review papers. The first is by Chandler 15 and focuses on a molecular description of the hydrophobic effect, while the second is by Sloan 16 and deals with gas hydrates.…”
Section: Introductionmentioning
confidence: 99%